2021
DOI: 10.1063/5.0059175
|View full text |Cite
|
Sign up to set email alerts
|

Noise induced suppression of spiral waves in a hybrid FitzHugh–Nagumo neuron with discontinuous resetting

Abstract: A modified FitzHugh-Nagumo neuron model with sigmoid function-based recovery variable is considered with electromagnetic flux coupling. The dynamical properties of the proposed neuron model are investigated and as the excitation current becomes larger, the number of fixed points decreases to one. The bifurcation plots are investigated to show the chaotic and periodic regimes for various values of excitation current and parameters. A network of the neuron model is constructed to study the wave propagation and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…In the following, we looked at the influence of BM noise [51,52] on observed SW in the array of FJJ by distributing it in two distinct ways. Firstly, the behavior of the network is analyzed by distribution noise throughout the simulation time.…”
Section: Impact Of Box-muller (Bm) Noise In a Network Of Fjjmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, we looked at the influence of BM noise [51,52] on observed SW in the array of FJJ by distributing it in two distinct ways. Firstly, the behavior of the network is analyzed by distribution noise throughout the simulation time.…”
Section: Impact Of Box-muller (Bm) Noise In a Network Of Fjjmentioning
confidence: 99%
“…Furthermore, noise is ubiquitous and can inevitably exist in many practical systems [51,52]; a wide range of studies have been conducted in the literature to explore the impacts of noise in dynamical systems. In particular, state-dependent noise is used to suppress chaos in fractional order chaotic systems [53].…”
Section: Introductionmentioning
confidence: 99%
“…From dynamical viewpoint, numerical approach can be used to detect the suitable coupling intensity for stabilizing complete synchronization via bifurcation analysis, calculating the Lyapunov exponents and using saturation gain method. [56] Indeed, the application of master stability function [57][58][59][60] provides helpful guidance to discern the possibility of synchronization control in dynamical systems. In fact, it is more worth investigating the collective behaviors and synchronization stability in memristive neural networks [61][62][63][64] considering the effect of time delay and parameter perturbations by applying feasible schemes.…”
Section: -7mentioning
confidence: 99%
“…In addition, it is found that there are very complex dynamic phenomena in the FHN model. Rajagopal et al (10) studied chaos and periodic bifurcation diagrams under different excitation currents and found that the dynamic behavior of the nodes alters dramatically after the introduction of Gaussian noise.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is found that there are very complex dynamic phenomena in the FHN model. Rajagopal et al ( 10 ) studied chaos and periodic bifurcation diagrams under different excitation currents and found that the dynamic behavior of the nodes alters dramatically after the introduction of Gaussian noise. Iqbal et al ( 11 ) studied robust adaptive synchronization of a ring-coupled uncertain chaotic FHN model and proposed a scheme to synchronize the coupled neurons under external electrical stimulation.…”
Section: Introductionmentioning
confidence: 99%